Purchase Intention to Actual Purchasing of Halal Cosmetics in Indonesian Young Adults in The Covid-19 Pandemic - Dwi Nastiti; Moh Fakhrurozi; Aditya Pratama (Jurnal Ilmiah Ekonomi Islam, 2022)
The Covid-19 outbreak initially had an impact on public health and began to penetrate the economy. Almost all industries were affected which caused many layoffs to occur. The cosmetic industry has become an anomaly, the Ministry of Industry pointed out, there has been an increase in online transactions for cosmetic products by up to 80 percent during this pandemic. This study aims to analyze several variables that can increase actual purchases during the Covid-19 pandemic on halal cosmetic products. Several variables that are thought to influence the actual purchase are perceived behavioral control, attitudes, and purchase intentions. This study uses a quantitative method with a population of young adult consumers who use cosmetics in Indonesia, with a sample of 400 respondents, with non-probability quota sampling, and a questionnaire with 14 question indicators. The data analysis used is SEM-PLS analysis using SmartPLS 3.3.3. The results show that the perceived behavioral and attitude control variables affect purchase intention, while the subjective norm variable does not affect purchase intention. Purchase intention has a significant effect on actual purchases during the Covid-19 pandemic. The results of this study show that the perceived behavioral and attitude control variables have a significant effect on purchase intention, while the subjective norm variable does not affect purchase intention. This study also shows that purchase intention has a significant influence on actual purchases during the Covid-19 pandemic. The results of this study show that the perceived behavioral and attitude control variables have a significant effect on purchase intention, while the subjective norm variable does not affect purchase intention. This study also shows that purchase intention has a significant influence on actual purchases during the Covid-19 pandemic.